Suatu Kajian Mengenai Keterkaitan Faktor-Faktor Pembentukan Karakter dalam Kitab Amsal - Farel Yosua Sualang (HUPERETES: Jurnal Teologi dan Pendidikan Kristen, 2023)
The book of Proverbs places a lot of emphasis on the vertical relationship between God and humans, as well as the horizontal relationship between human beings. Not surprisingly, the teachings of wisdom in the book of Proverbs offer an antithesis in one's life between wise and stupid traits that contribute to character building. However, the study of the factors of character formation in the book of Proverbs is still a matter of debate (especially Brown and Bland's interpretation). The purpose of this study is to find a relationship between the factors forming the character in the book of Proverbs, along with its elements. By using a literature study, this article describes as many sources as possible to obtain the factors of character formation in the book of Proverbs. Therefore, it is found that there are three factors of character formation in the book of Proverbs (along with their respective elements) that are interrelated, namely First, the fear of the Lord factor (the elements are experience observation, self-awareness, character transformation and imitation), secondly the character-consequence factor (The elements are the role of conscience, belief, intention, decision-making, character evaluation, and character habituation), the three factors of moral instruction through the role of the family (the elements are imitation, reprimand and upbringing of parents, character evaluation, and character habituation).Kitab Amsal banyak memberikan penekanan terhadap hubungan vertikal antara Tuhan dan manusia, begitupun hubungan horizontal antara sesama manusia. Tidaklah heran, ajaran hikmat dalam kitab Amsal menawarkan tentang suatu antitesis kehidupan seseorang antara sifat-sifat bijak dan bebal yang memiliki kontribusi kepada pembentukan karakter. Namun begitu, kajian mengenai faktor-faktor pembentukan karakter dalam kitab Amsal masih menjadi suatu perdebatan (khususnya interpretasi Brown dan Bland). Tujuan penelitian ini adalah ingin menemukan suatu keterkaitan faktor-faktor pembentukan karakter dalam kitab Amsal beserta dengan elemen-elemennya. Dengan menggunakan studi literatur, artikel ini memaparkan sebanyak mungkin sumber untuk memperoleh faktor-faktor pembentukan karakter dalam kitab Amsal. Oleh sebab itu, ditemukan  adanya tiga faktor pembentukan karakter dalam kitab Amsal (beserta elemennya masing-masing) yang saling terkait yaitu: Pertama, Faktor takut akan Tuhan (elemennya adalah observasi pengalaman, kesadaran diri, transformasi karakter dan imitasi); Kedua faktor karakter-konsekuensi (elemennya adalah peran hati nurani, keyakinan, niat, pengambilan keputusan, evaluasi karakter, dan pembiasaan karakter); Ketiga faktor instruksi moral melalui peran keluarga (elemennya adalah imitasi, teguran dan didikan orang tua, evaluasi karakter, dan pembiasaan karakter).